Persistent elevated serum levels of intact parathyroid hormone after reoperation for primary hyperparathyroidism and after pamidronate therapy - Darcan, Sükran; Coker, Mahmut; Aydinok, Yeşim; Gökşen, Damla; Ozok, Geylani (The Turkish Journal of Pediatrics, 2003)
Primary hyperparathyroidism is a life-threatening rare disorder. It is seen as a result of neonatal primary hyperparathyroidism, familial hypocalciuric hypercalcemia, increased vitamin D levels and inactivation of calcium sensing receptor mutations. The clinical findings are hypotonia, bone demineralization, hypercalcemia and parathyroid hyperplasia. We present a six-month-old female patient, the first child of nonconsanguineous parents, who was referred for the investigation of failure to thrive, vomiting, constipation, fever, abdominal distention and hypotonia. Physical examination revealed weight under 3rd percentile, height 3rd-10th percentile, decreased subcutaneous fat, and distention of the abdomen. In neurological examination, hypotonia, motor-mental retardation, and active deep tendon reflexes were found. The biochemical values at the time of admission revealed primary hyperparathyroidism. Since hypercalcemia did not respond to calcitonin therapy and due to the mortality of hypercalcemia, parathyroidectomy was performed. Because hyperparathyroidism and hypercalcemia continued, angiography was done which revealed increased parathyroid hormone levels in the periphery of the innominate vein. Exploratory surgery followed, but hyperparathyroidism and hypercalcemia persisted after all of these procedures. Calcium-sensing receptor mutations and supernumerary gland were considered. Because hypercalcemia persisted, pamidronate therapy was initiated on a monthly basis.